Covid-19: Network Effectiveness of Intermunicipal Self-Organized Response in Chile - Arias-Yurisch, K; Retamal-Soto, K; Ramos-Fuenzalida, C (Babes-Bolyai University, 2020)
In the context of the Covid-19 pandemic, public officials are called on to implement different strategies in order to respond effectively. One of the lessons of emergency management research is that effective response is unlikely without col-laboration. Research on collaborative emergency management has focused on measuring the effectiveness of intergovernmental and intersec-toral relationships, but little is known about the performance of inter-jurisdictional collaboration. This paper seeks to measure the network effectiveness of intermunicipal self-organized response to Covid-19. It uses a network analysis approach to compare planned and actual emergency management networks operating in the Santiago Metropolitan Region of Chile. Content analysis of 202 formal agreements established by municipalities in 2009-2019 was used to capture the planned network. The actual network was depicted by col-lecting original data through an online survey that represented the 96% of the local governments located in this Latin American city. The results show a structural gap between planned and actual networks and reveal effectiveness problems associated with the disaster preparedness phase. However, an emergent intermunicipal network has supported collaborative response to the Covid-19 pandemic. The study provides lessons for policy-makers, public managers and researchers in the collaborative emergency management field. © 2020, Babes-Bolyai University. All rights reserved.